If from the initial circles with curvature $k_a, k_b, k_c, k_d$ and centers $c_a, c_b, c_c, c_d$ you generate four new circles with curvatures: $k_e = 2(k_b+k_c+k_d) - k_a$ $k_f = 2(k_c+k_d+k_a) - k_b$ $k_g = 2(k_d+k_a+k_b) - k_c$ $k_h = 2(k_a+k_b+k_c) - k_d$ Those circles have centers (complex plane): $c_e = \frac{2(k_bc_b +k_cc_c +k_dc_d) - k_ac_a}{k_e}$ $c_f = \frac{2(k_cc_c +k_dc_d + k_ac_a) - k_bc_b}{k_f}$ $c_g = \frac{2(k_dc_d +k_ac_a+k_bc_b) - k_cc_c}{k_g}$ $c_h = \frac{2(k_ac_a +k_bc_b +k_cc_c) - k_dc_d}{k_h}$ After the first step, each new circle can generate three more unique circles, i.e., if a circle e is created with a, b, c, d then three new circles can be generated with: $k_f = 2(k_c+k_d+k_e) - k_b$ $k_g = 2(k_b+k_d+k_e) - k_c$ $k_h = 2(k_c+k_b+k_e) - k_d$ $c_f = \frac{2(k_cc_c +k_dc_d +k_ec_e) - k_bc_b}{k_f}$ $c_g = \frac{2(k_bc_b +k_dc_d + k_ec_e) - k_cc_c}{k_g}$ $c_h = \frac{2(k_cc_c +k_bc_b+k_ec_e) - k_dc_d}{k_h}$